Biographische Analysen zum Verhältnis von Selbstwert und Beruf - Lubecki, Verena (Forum Komparative Kasuistik, 2009)
The research interest of this work is the systematic comparison of biographical case studies of professional social workers and people from the natural sciences in relation to the psychological constructs of self-esteem and autogenesis. It is based on the comparatives casuistry as research method. For collection and analysis, the problem-centered interview and the circular deconstruction were elected.